Mengapa Decision Memilih Bank Syariah Rendah? Membaca Peran dalam Mempengaruhi Interest Student - Yuwan Ferdiana Ilahi; Munirul Abidin; Eko Suprayitno; Ceta Indra Lesmana (JURNAL ILMIAH GEMA PERENCANA, 2025)
Even though Indonesia is home to the largest number of Muslims worldwide, the number of people who use Islamic banking services is still somewhat lower than that of conventional banks. The purpose of this study is to identify the factors that make student less inclined to choose a syariah bank. This study examines how the environment and perceptions affect confidence and adherence to using a syariah bank by using a quantitative deskriptif method and through SmartPLS analysis. The analysis's findings indicate that the environment has a significant impact on perception, with a koefisien of 0.185 (p < 0,001). Perception also has a positive impact on interest, with a coefficient of 0.417% (p < 0,001). Perception, however, does not indicate a significant impact on decision, with a koefisien of 0.138 (p = 0,074). In addition, interest proven has a significant impact on decision, with a coefficient of 0.709 (p < 0,001). This finding indicates that perception mediates the influence of the environment on interest, The student's final decision is imperceptibly affected by their interest regarding syariah bank products. The results indicate that there are significant effects of the environment on perception, with perceptions influencing the relationship between the environment and interest. However, Perception does not indicate a significant impact on decision, indicating that there is a lack of agreement between interest and nyata. All of this provides a strategic plan to help syariah banks increase their positive credit and turn their interest into a nyata decision.